Neurophysiological error processing and addiction self‐awareness correlates of reduced insight in cannabis use disorder. - Macatee, Richard J.; Schermitzler, Brandon S.; Minieri, Jessica B.; Moeller, Scott J.; Afshar, Kaveh; Preston, Thomas J. (Addiction, 2023)
Background and Aims: Cannabis use disorder (CUD) prevalence has increased, while perceived risks of cannabis use and CUD treatment need have decreased. Chronic cannabis use may also impair the neural and behavioral mechanisms of insight, further hampering treatment‐seeking. This study aimed to measure whether CUD is characterized by reduced self‐monitoring in drug‐related contexts (objectively‐assessed insight), subserved by functional neural abnormalities in error‐processing and manifested clinically as decreased awareness of the need to change. Design: Case–control laboratory study was used. Setting: University setting was in Alabama, USA. Participants: There were 42 CUD participants and 47 age‐, sex‐, and nicotine use‐matched controls. Measurements: Participants completed a probabilistic choice task, adapted for the first time for CUD, in which they selected pleasant, unpleasant, neutral, and cannabis‐related images according to their preference. Reduced versus accurate insight was operationalized as the correspondence between self‐reported and actual most chosen image type. Neurophysiological error‐processing during an inhibitory control task was recorded using electroencephalography. Participants with CUD completed measures of cannabis problem recognition and motivation to change. Findings Compared with controls, the CUD group made significantly more cannabis selections on the choice task (mean difference [MD] = 8.11, 95% confidence interval [CI] [4.88 11.35], p < 0.001) and had significantly reduced insight into cannabis choice (odds ratio [OR] = 9.69, 95% CI [1.06 88.65], p = 0.04). CUD participants with reduced insight on the choice task had significantly decreased neurophysiological reactivity to errors on the inhibitory control task (error‐related negativity) compared with CUD participants with accurate insight (MD = 2.64 μV, 95% CI [0.74 μV 4.54 μV], p = 0.008) and controls (MD = 4.05 μV, 95% CI [1.29 μV 6.80 μV], p = 0.005). Compared with CUD participants with accurate insight on the choice task, CUD participants with reduced insight reported significantly less agreement that they had a cannabis problem (MD = ‐5.06, 95% CI [−8.49–1.62], p = 0.003). Conclusions: People with CUD who show reduced insight on a drug‐related choice task may also have decreased early neural error‐processing and less cannabis problem recognition.